2020
DOI: 10.1002/anie.202007651
|View full text |Cite
|
Sign up to set email alerts
|

Formyl MIDA Boronate: C1 Building Block Enables Straightforward Access to α‐Functionalized Organoboron Derivatives

Abstract: Formyl MIDA boronate has been known to be an elusive type of acylboronate that has not been obtained to date. In this work, an approach to the one‐pot preparation and chemical transformations of formyl MIDA boronate were developed to provide new types of α‐functionalized organoboron compounds. Among them are acylboronate reagents which present boron‐substituted analogues of ynones and β‐dicarbonyl compounds. The developed synthetic procedures, utilizing formyl MIDA boronate, are tolerant to diverse functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…This allows for the preparation of various functionalized MIDA boronate building blocks, including, for example, unusual acyl derivatives 16-18 shown in Figure 4. [124][125][126][127] It should be outlined that some aspects of the aforementioned approaches (i. e. the CÀ B bond formation via radical intermediates, [128] as well as transition metal-free methods [129] ) were recently reviewed.…”
Section: Synthesis Of Saturated (Hetero)aliphatic Boronatesmentioning
confidence: 99%
“…This allows for the preparation of various functionalized MIDA boronate building blocks, including, for example, unusual acyl derivatives 16-18 shown in Figure 4. [124][125][126][127] It should be outlined that some aspects of the aforementioned approaches (i. e. the CÀ B bond formation via radical intermediates, [128] as well as transition metal-free methods [129] ) were recently reviewed.…”
Section: Synthesis Of Saturated (Hetero)aliphatic Boronatesmentioning
confidence: 99%
“…Note added in proof : Since the submission of this Minireview, Grygorenko and co‐workers reported the synthesis of formyl MIDA boronate. Treatment of this building block with organotitanium reagents followed by Dess Martin/Swern oxidation produced alkynyl acylboronates …”
Section: Discussionmentioning
confidence: 99%
“…Allenylation of aldehydes with propargyl derivatives bearing an appropriate leaving group (normally bromides) represent another classical approach for the allenol synthesis. Many reports have appeared dealing with the regioselective control between propargylation and allenylation, including a wide variety of metal catalysts, such as Sn complexes, 57 59 Zn, 60 62 Bi, or Cd salts. 63 Among all these well-known procedures, In-promoted allenylation in aqueous media has possibly provided the best results.…”
Section: Synthesis Of Allenolsmentioning
confidence: 99%
“…Allenylation of aldehydes with propargyl derivatives bearing an appropriate leaving group (normally bromides) represent another classical approach for the allenol synthesis. Many reports have appeared dealing with the regioselective control between propargylation and allenylation, including a wide variety of metal catalysts, such as Sn complexes, Zn, Bi, or Cd salts . Among all these well-known procedures, In-promoted allenylation in aqueous media has possibly provided the best results. In this field, Cr-catalyzed allenylation of aldehydes is probably the only contribution appeared during the past decade, allenols are prepared in a complete regioselective manner allowing both racemic and enantioselective synthesis, with the late being further discussed in the next section …”
Section: Synthesis Of Allenolsmentioning
confidence: 99%